Influence of sowing date on occurrence of spot blotch and yield of wheat varieties in eastern Uttar Pradesh - and S.S.L. SRIVASTAVA, S.K. BISWAS* (Indian Phytopathology, 2010)
Five popular varieties viz. Sonalika, WH 147, HD 2329, K 9107, HUW 234 were grown on different sowing dates at 15 day’s interval during Rabi season showed that optimum time of sowing for all the five varieties is 15th November followed by 30th October. The early sown crop was less affected by spot blotch than late sown crop and resulted higher in yield. The maximum with 76.76, 49.61 and 59.12 per cent disease incidence in variety WH 147 and minimum 41.03, 44.21 and 51.73 per cent in K 9107 was recorded in all three consecutive years from 30th December sowing date. Yield of wheat was also affected by date of sowing. Higher yield is obtained from 15th November date of sowing. Among five popular wheat varieties, HD 2329 recorded highest yield with 43.0, 41.78 and 39.71 q/ha against lowest 39.0, 37.0 and 35.52 q/ha in HUW 234 at 15th November date of sowing in all the three consecutive years. The pooled analysis data on disease severity and yield of crop was also showed the similar trend of observation as it found in respective years.